INDICATORS OF STRUCTURAL AND FUNCTIONAL CHANGES IN THE MYOCARDIUM AS PREDICTORS OF THE ATRIAL FIBRILLATION IN PATIENTS WITH HEART FAILURE AND PRESERVED EJECTION FRACTION - Cherniaieva, Kateryna; Rudenko, Yuliia; Mostbauer, Galyna; Bezrodniy, Andrii; Shevchuk, Mykhailo; Sablin, Andrii; Moskalenko, Yuliia; Kovtun, Evgen (The Ukrainian Scientific Medical Youth Journal, 2019)
A large number of recent trials suggested that atrial fibrillation (AF) and heart failure (HF) should be considered as two epidemic cardiovascular pathologies that are closely interrelated, each contributing to the development of the other. The purpose of our work was to analyze the peculiarities of the structural and functional parameters of the heart and blood vessels in patients with HFpEF, as well as to determine the most informative predictors of AF and their predictive value. A study of the literature indicates that AF has a close relationship with both HFpEF and the diagnostic criteria used to determine it. The relevance of the study of this pathology is that AF has a significant impact on the course and prognosis of HFpEF. The study was conducted on a case-control design. This work is based on the results of ex- amination of 115 hemodynamically stable patients with arterial hypertension (AH), clinical symptoms and signs of heart failure (HF), with left ventricular (LV) ejection fraction (EF) ≥ 50% and signs of diastolic dysfunction (DD) according to echocardiography data. Patients’ age ranged from 40 to 85 years (mean age 66.3 ± 10.8 years). For the first time, criteria for LV DD were analyzed as possible predictors of atrial fibrillation in patients with HFpEF and thresholds for some of them were determined. The study empirically confirms and theo- retically argues that the presence of atrial fibrillation in patients with HFpEF, in contrast to those with sinus rhythm, is associated with a more severe functional class of HF estimated by NYHA classification; higher by 28.1% NTprоBNP level; increased left ventricular filling pres- sure with LAVI thresholds > 40 ml/m2 and E/e ‘> 14.75; with impaired endothelium-depen- dent vasodilation and an initial decrease in glomerular filtration rate. The results of the study may be useful for the screening and detection of AF in patients with established HFpEF, by monitoring of ECG, in case of detection of threshold values of diastolic LV dysfunction.